"But big is a funny word": a multiple perspective on concept formation in a foreign-language-mediated classroom. Issue 1 (24th August 2015) - Alanen, Riikka; Jäppinen, Aini-Kristiina; Nikula, Tarja
Abstract : In recent years, foreign-language mediated instruction (immersion, content-based language learning and teaching) has been studied from various perspectives. In the following study, a single event from a Finnish third-grade EFL-mediated geography lesson is studied by combining insights from three research approaches: sociocultural, socio-cognitive, and discourse-pragmatic. The data analysis focuses on how during concept formation, the participants use commonplace means present in every classroom – textbook and chalkboard, spoken and written, verbal and nonverbal communicative means – to construct knowledge and its social context. The results indicate that there exist strong parallels among the ways the various means are used by the participants in the activity, and that this pattern coincides with the changes in the teacher's control of classroom interaction. Methodologically, the multiple perspective adopted in the study highlights the nature of social interaction and the complex issues involved in the teaching and learning processes in the classroom context.